2018
DOI: 10.1364/ol.43.002523
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser writing of photonic devices in borate glasses compositionally designed to be laser writable

Abstract: The design and performance of borate glass samples compositionally pre-designed to be femtosecond laser writable via laser-induced ion migration is reported in this Letter. It is demonstrated that borate glasses modified on purpose with small amounts of LaO and NaO can be straightforwardly used to produce high-index contrast (Δn) waveguides by femtosecond-laser-assisted ion migration. The positive Δn of the waveguides is caused by the local enrichment of LaO in the guiding region with a slope of 8·10(mol.%). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 27 publications
10
21
0
Order By: Relevance
“…written at 695 nJ in PS03. This additional migration pole has been also observed in other glasses (borates) upon waveguide writing via FLIER [17]. Figure 2a.…”
Section: Morphology Of the Structures Guiding Performance And Refracsupporting
confidence: 71%
See 3 more Smart Citations
“…written at 695 nJ in PS03. This additional migration pole has been also observed in other glasses (borates) upon waveguide writing via FLIER [17]. Figure 2a.…”
Section: Morphology Of the Structures Guiding Performance And Refracsupporting
confidence: 71%
“…However, higher contents of La 2 O 3 will produce a lack of enough terminal oxygens to coordinate all La 3+ , giving rise to formation of La-O-La bonds that will affect density and refractive index non-linearly. This index modification mechanism has also been confirmed in the case of a borate glass matrix, where, due to the different initial matrix density, the local index increase versus the local La 3+ content is much stronger [17].…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…It is worth noting that fs‐laser induced local modification of the glass composition has been shown to provide an extremely efficient alternative for the production of high performance passive waveguides, waveguide optical amplifiers and lasers . We have shown that in several glass families including phosphates, tellurites, and borates, it is feasible producing high contrast waveguides by inducing the migration of an index carrier element (La, Te, …) toward the guiding region by fs‐laser irradiation at high repetition rate. The migration of the carrier index element occurs along with the cross migration of a fast diffusing element, normally an alkaline (Na, K).…”
Section: Introductionmentioning
confidence: 98%